Construction of ice domes at Asuka Station in Antarctica - Kenji Ishizawa; Tsutomu Kokawa; Toshio Hannuki (National Institute of Polar Research, 1993)
An attempt was made to construct an ice dome in order to study the construction technique and to examine its deformation by creep and sublimation of ice in the Antarctic. A 10-m diameter membrane was inflated by a ventilator. Stored water was sprayed on it, and sometimes milled snow was blown by a small snow miller. About 13t of water was consumed for making an ice dome 7cm thick, 3m high. The deformation of the ceiling grew with time due to creep. The sinkage of the center reached 55mm after 99 days. The wall thickness rapidly decreased due to sublimation in summer time; consequently, snow was occasionally added with a rotary snowplow. The ice dome was effectively used as storehouse and workshop. Though it was attmpted to make water outside by using a snow melter with an oil burner for another ice dome, the work was hard. A snow dome without water was also attempted, but the snow did not harden.